Monitoring of Air Temperature and Humidity Inside and Outside Oyster Mushroom (Pleurotus ostreatus) House Using DHT11 Sensor - Widhiantari, Ida Ayu; Widiastawan, I Kadek Widi; Prasistha, Ni Ketut Intan (Jurnal Online Pertanian Tropik, 2025)
Oyster mushrooms (Pleurotus ostreatus) require a humid environment and stable temperatures to grow optimally. One of the mushroom growing media, namely mushroom house, which need to be regulated in temperature and humidity in order to produce high-quality mushrooms. Management of environmental conditions is essential, as significant changes in temperature and humidity can inhibit mold growth or even cause disease. This study aims to monitor the internal and external conditions of the oyster mushroom growing environment using a DHT11 sensor so that ideal growth conditions can be obtained. This research was carried out through several stages, including the preparation of tools and materials, hardware design, layout arrangement, testing of temperature and air humidity control systems, and monitoring oyster mold growth. The results of the 20-day study showed that the internal temperature in oyster mushroom clusters was at the ideal temperature for oyster mushroom growth, which ranged from 25,3°C to 30,8°C, while the maximum humidity reached up to 98% at certain times. The external temperature of mushroom house is in the temperature range of 28°C to 33,5°C with a relatively lower humidity, ranging from 73,2% to 91,2%. Humidity above 90% dominates most measurements, especially in the afternoon, creating ideal conditions for mold growth. The use of the DHT11 sensor in temperature and humidity measurements in this study was effective in recording significant daily fluctuations. The resulting data shows that the sensor is able to detect changes in temperature and humidity of the kumbung chamber and the environment.